THE READABILITY LEVEL OF THE READING TEXT IN “PATHWAY TO ENGLISH” BY ERLANGGA FOR XI OF SENIOR HIGH SCHOOL - Rohmanita Riski Istikhomah; Muh Syafei; Nuraeningsih Nuraeningsih (Universitas Muria Kudus, 2023)
Abstract: The objective of the research was to find out the readability level of reading text in Pathway to English by Erlangga of 2017 edition for XI of Senior High School, which is generally used in the school as a written source and used by the teacher to deliver the material. This research is categorized as descriptive quantitative research and the data was collected and analyzed using Flesch Reading Ease formula. The results of this research show that 17 from 20 reading text is readable for XI of Senior High School, 2 of them is for the 13th to 16th grade, and 1 reading text is for College Graduate. Then, the average of readability score of the reading text is 62.88, which can interpret that Pathway to English for XI of Senior High School by Erlangga of 2017 edition for Kelompok Peminatan in Standard level and it’s readable for 10th to 12th grade, which can be concluded that this textbooks is readable and appropriate for XI of Senior High School.